PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) MENGGUNAKAN OUTING KELAS BERBASIS PROBLEM BASED LEARNING(PBL) PADA MATERI KLASIFIKASI MAKHLUK HIDUP KELAS VII SMP - Nika, Kristina; Hadi Jaya Putra, Sukarman; S, Mansur (Jurnal Biogenerasi, 2024)
This study aims to develop Student Worksheets (LKPD) based on the Problem-Based Learning (PBL) model to enhance students' cognitive learning outcomes on the topic of Classification of Living Things at SMP Negeri 1 Mego. This development is expected to create effective and inclusive learning media, accommodating students' needs across diverse abilities and backgrounds, while supporting understanding of complex biological concepts.\n\nThe research was conducted using the Research and Development (R&D) model, which includes the stages of needs analysis, product design, expert validation, small- and large-scale trials, and product revision. The research subjects were seventh-grade students at SMP Negeri 1 Mego with varying levels of learning ability. Data were collected through observation, questionnaires, and interviews involving teachers and students.The results showed that the developed LKPD received excellent validation scores from experts. Validation by subject matter experts scored 96.88%, by language experts 100%, and by media experts 96.25%, all categorized as highly valid. The small-scale trial yielded feasibility levels of 89.68% according to students and 89.5% according to teachers, both categorized as highly feasible. In the large-scale trial, feasibility levels increased to 93.7% according to students and 100% according to teachers, also categorized as highly feasible.\n\nBased on these findings, the PBL-based LKPD is proven to be effective i